A study on the structural analysis of aluminium drosses and processing of industrial aluminium salty slags - Hazar, ABY; Saridede, MN; Çigdem, M (WILEY, 2005)
In aluminium-melting operations, a dross layer containing 85% metallic Al forms on the surface of the molten aluminium bath. Therefore, a significant amount of metal is removed from the furnace with the dross. Melt losses are one of the most important economical points in the melting operations. In the first part of the present study, a series of reverbaratory furnace drosses received from several aluminium plants located in Turkey were examined to determine their compositional and structural characteristics. Following crushing and grinding operations, drosses were dimensionally classified into 5 groups. Metallic Al, Mg, Zn, Fe and SiO2 contents of each group were analyzed separately. The metallic aluminium content of the group +4 mm is found to be approximately 75% while that of -0.5 mm group is 25%. Another fundamental finding is the high Mg content present in the drosses. Furthermore, Fe and SiO2 contents increase with decreasing particle size of the dross. In the second part of the investigation, experiments were carried out on the treatment of the salty slags to obtain salt, aluminium and non-metallic products which can be used for various purposes. Leaching and crystallization in an evaporator is employed to determine the optimum conditions for the recovery of flux from the salty slag.
Keywords: aluminium dross; crystallization; leaching; recovery; salty slag; structural analyses; Metallurgy & Metallurgical Engineering